"That Indefinite Area of Toleration": Criminal Conspiracy and Trade Unions in Ontario, 1837-77 - Tucker, Eric (Labour / Le Travail, 1991)
During the first three quarters of the nineteenth century, the question of whether trade unions in Ontario were criminal conspiracies under common law was never clearly determined. By examining the development and interaction of the legal and social zones of toleration we can illuminate how law was shaped by and shaped early struggles between workers and employers. The statutory reforms of 1872 clearly defined a narrow zone of legal toleration in which trade unions were accepted as labour market organizations while the means they could to pursue their objectives were restricted. The contours of industrial legality which began to emerge during this period remain a salient feature of current labour law.
Keywords: CONSPIRACIES; CONSPIRACY theories; Industrial relations; LABOR laws & legislation; LABOR supply; Labor Unions; Labor movement; Ontario; POLITICAL crimes & offenses

Back to Work? Labour, State, and Industrial Relations in Canada - Tucker, Eric (Labour / Le Travail, 1991)
The article reviews the book, "Back to Work? Labour, State and Industrial Relations in Canada," by Bob Russell.
Keywords: BACK to Work: Labour, State & Industrial Relations in Canada (Book); BOOKS -- Reviews; Industrial relations; Nonfiction; RUSSELL, Bob